Ophthalmoscopy in dog and cat - LIAPIS (Ι. Κ. ΛΙΑΠΗΣ), I. Κ. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ophthalmoscopy is the procedure for fundus examination. As an examining technique, ophthalmoscopy is based on the principles of reflection and refraction of the light. In the first case (reflection of the light) ophthalmoscopy is direct. In the second case (reflection and refraction of the light) ophthalmoscopy is indirect. For direct ophthalmoscopy a simple light source is used or better yet a special ophthalmoscope. The indirect technique is realised with the assistance of special equipment. Each one of the above mentionned methods has advantages and disadvantages and it's better having them coherent to one another. The indirect ophthalmoscopy gives a general view of the fundus and magnifies it satisfactorily, whereas direct ophthalmoscopy even though provokes better magnification, gives a smaller optical field.